GENOMIC PROFILING OF PRIMARY AND MATCHED RECURRENT GLIOBLASTOMA TUMOURS REVEALS THAT THE MUTATIONAL LANDSCAPE INCLUDES CLINICALLY ACTIONABLE VARIATION. (3rd October 2018) - McInerney, Caitríona; Ellis, Hayley; Schrinpf, Daniel; Sahm, Felix; Stupnikov, Alexei; Wadsley, Marc; Wragg, Christopher; White, Paul; McArt, Darragh; Kurian, Kathreena
Abstract: Glioblastomas account for 90% of adult brain tumours and patient survival remains low. Understanding genetic alterations in subtypes could improve therapeutic intervention. Tumours from 41 patients, 8 with matched recurrent glioblastomas were genomically profiled for 130 neuro-oncology genes using a diagnostic panel. Single nucleotide variants(SNVs), copy number variations(CNVs) and potentially clinically actionable mutations were assessed for IDH-wildtype(n=38) and IDH-mutant glioblastomas(n=3). Mutational landscape revealed discrete differences and similarities between subtypes. TSC2, MSH6, TP53, CREBBP and IDH1 were co-mutated and putatively pathogenic in both subtypes, suggesting they are driver mutations. Recurrent tumours were not hypermutated and matched analysis revealed inter-tumour heterogeneity. IDH-wildtype: SNVs(145) impacted RTK/Ras/PI(3)K(82%), p53(63%), WNT(58%), SHH(13%), NOTCH(11%), Rb(5%) and G-protein(8%) pathways. SNV burden was a predictor of overall survival(P = 0.003) but no pathway was individually responsible. SNVs(40) in BRAF, DAXX, EGFR, FGFR2, JAK2, MYB, PIK3CA, PIK3R1, PTEN, ATM, BRCA1, CHEK2, PPM1D, PTCH1 and SMO were also putatively pathogenic. Many initial tumours had BRCA1/2(21;18%) variants, including confirmed somatic mutations in haemangioblastoma. Survival analysis suggested GNAS variation was prognostic(P<0.001). Recurrent tumours had fewer pathways(RTK/Ras/PI(3)K, p53, WNT, G-protein) impacted by genetic alterations. Possible resistance signatures included a private mutation in PIK3C2G and CNV gains(BRCA2, GNAS, EGFR) and losses(TERT, SMARCA4). Recurrent tumours(57%;4/7) harboured potentially actionable variation in PTEN, BRCA1, BRCA2, ATR and EGFR. Combination therapies with erlotinib, everolimus or dasatinib, olaparib, ATR inhibitors and EGFR-targeting antibodies, vaccines or TK inhibitors could provide therapeutic intervention. IDH-mutant: SNVs(15) impacted RTK/Ras/PI(3)K(66%), p53(100%) and WNT pathways(33%). SNVs were also putatively pathogenic in KLK1 exclusively in this subtype. The recurrent tumour had fewer pathways(p53, WNT, G-protein) impacted by genetic alterations and a private mutation in TCF4. Potentially actionable variation in ATR could be targeted using inhibitors. In conclusion, TCGA-GBM and GDC datasets corroborated results confirming the clinical significance of findings. Combination therapies targeting subtype clinically actionable mutations may hold the best promise for patient oncological management.